Age-Dependent Relationship Between Plasma Aβ40 and Aβ42 and Total Tau Levels in Cognitively Normal Subjects - Lue, Lih-Fen; Pai, Ming-Chyi; Chen, Ta-Fu; Hu, Chaur-Jong; Huang, Li-Kai; Lin, Wei-Che; Wu, Chau-Chung; Jeng, Jian-Shing; Blennow, Kaj; Sabbagh, Marwan N.; Yan, Sui-Hing; Wang, Pei-Ning; et al. (Frontiers in Aging Neuroscience, 2019)
Both amyloid plaques and neurofibrillary tangles are pathological hallmarks in the brains of patients with Alzheimer’s disease (AD). However, the constituents of these hallmarks, amyloid beta (Aβ) 40, Aβ42, and total Tau (t-Tau), have been detected in the blood of cognitively normal subjects by using an immunomagnetic reduction (IMR) assay. Whether these levels are age-dependent is not known, and their interrelation remains undefined. We determined the levels of these biomarkers in cognitively normal subjects of different age groups. A total of 391 cognitively normal subjects aged 23–91 were enrolled from hospitals in Asia, Europe, and North America. Healthy cognition was evaluated by NIA-AA guidelines to exclude subjects with mild cognitive impairment (MCI) and AD and by cognitive assessment using the Mini Mental State Examination and Clinical Dementia Rating (CDR). We examined the effect of age on plasma levels of Aβ40, Aβ42, and t-Tau and the relationship between these biomarkers during aging. Additionally, we explored age-related reference intervals for each biomarker. Plasma t-Tau and Aβ42 levels had modest but significant correlations with chronological age (r = 0.127, p = 0.0120 for t-Tau; r = −0.126, p = 0.0128 for Aβ42), ranging from ages 23 to 91. Significant positive correlations were detected between Aβ42 and t-Tau in the groups aged 50 years and older, with Rho values ranging from 0.249 to 0.474. Significant negative correlations were detected between Aβ40 and t-Tau from age 40 to 91 (r ranged from −0.293 to −0.582) and between Aβ40 and Aβ42 in the age groups of 30–39 (r = −0.562, p = 0.0235), 50–59 (r = −0.261, p = 0.0142), 60–69 (r = −0.303, p = 0.0004), and 80–91 (r = 0.459, p = 0.0083). We also provided age-related reference intervals for each biomarker. In this multicenter study, age had weak but significant effects on the levels of Aβ42 and t-Tau in plasma. However, the age group defined by decade revealed the emergence of a relationship between Aβ40, Aβ42, and t-Tau in the 6th and 7th decades. Validation of our findings in a large-scale and longitudinal study is warranted.